Translation in the Era of Globalisation - AKPACA, SERVAIS MARTIAL; MINAFLINOU-BANKOLE, Estelle; Olusegun, Afolabi (My University, 2021)
The globalisation process, which has brought about drastic changes in the global economy, has affected contemporary translation in many ways. As Michael Cronin (2003) puts it in Translation and Globalisation, ―if contemporary reality is inescapably multicultural and multinational, then it makes sense to look at a discipline which has mediation between cultures and languages as a central concern to assist us in understanding globalisation.‖ It is in this context that this paper aims to show that due to globalisation, translation is influenced by the rise of e-commerce and localisation as well as by automation, the rise of supra-national organisations, time constraints and the centrality of specific languages. The methodology of the paper is mostly descriptive. Indeed, the historical conditions that gave rise to globalisation are recalled briefly, and the link between translation and globalisation is described along the lines drawn by several authors including Denis Thouard, Michael Oustinoff and Joanna Nowicki, Louis-Jean Calvet and Michel Rochard. The major finding of the paper is that the way translation is done in the ICT era is different from the way it used to be done with pen and paper. Machine translation is quite successful in some institutions but in most cases, it is poor and needs to be revised. Major organisations use translation memories to save money and time. Translation remains a major medium for the spread of knowledge. The centrality of a few languages in the global system of translation is putting peripheral languages at risk.
Keywords: Translation; globalisation; localisation; automation